Recognition of multiepitope dendrimeric antigens by human immunoglobulin E. - Montañez-Vega, María Isabel; Nájera-Albendín, Francisco; Mayorga Mayorga, Cristobalina; Ruiz-Sánchez, Antonio Jesús; Vida-Pol, Yolanda; Collado-Martín, Daniel; Blanca, Miguel; Torres-Jaén, María Josefa; Pérez-de-Inestrosa-Villatoro, Ezequiel (Elsevier, 2015)
In vitro drug allergy tests have limited sensitivity, partly due to a poor understanding of the immunological recognition of in vitro drug–protein conjugates. We have designed and synthesized multivalent mono- and bi-epitope dendrimeric antigen (DeAn) conjugates and studied their chemical and tridimensional structures. We describe differences in the spatial distribution and conformation of these conjugated epitopes for the first time: a partially hidden benzylpenicilloyl and a more exposed amoxicilloyl. Our data suggest that DeAn conjugates provide a useful model for studying IgE recognition in patients who suffer from an allergic reaction to benzylpenicillin and/or amoxicillin. 1D and 2D NMR, MDS and immunochemical studies provide evidence that both antigen composition and tridimensional distribution play key roles in IgE-antigen recognition. Bi-epitope DeAn conjugates could potentially allow the diagnosis of patients allergic to any of these two drugs with a single test and represent the basis for a broadly-applicable in vitro assay.
Keywords: Inmunoquímica; Dendrímeros; Antígenos; Immune response; Immunochemistry; Dendrimer